Ciclos nordestinos 1, 2 e 3 para piano de Marlos Nobre: uma abordagem analítico-interpretativa - Ferraz, Rachel Gico Casado (2007)
The object of this study is to analyze Marlos Nobre s Ciclos Nordestinos for piano through two distinct sources of theoretical referencial: the theoretical and practical knowledge of elements that compose folk/popular Brazilian music, specifically the one from the Northeastern region, and the style analysis of the method proposed by Jan LaRue. Marlos Nobre composed four Ciclos Nordestinos for piano but the fourth has not been approached for there is no revised revision up-to-date. The analysis of the Ciclos Nordestinos focused on the five parameters proposed by Jan LaRue: Sound, Harmony, Melody, Rhythm and Growth. It is also included observations about technical aspects and performance suggestions. The analyses show the existence of a great difference of level of performance between the First one and the Third Cycles; the asymmetry in the three Cycles compared between themselves in relation to the indication of speed and character; the existing quotation removed of the folk/popular origin; and the concern of the composer in placing some possibilities of study for a pupil of the piano, however, most important of them is the dissociation between left hand and right hand.